In vitro Cytotoxicity Evaluation of Dandelion Root Ethanol Extract on PANC-1 Cell Line - Aras, Aliye İrem; Arslan, Emine; Özçay, Büşra (Universitas Muhammadiyah Yogyakarta, 2024)
A challenging diagnosis is the outcome of pancreatic cancer's aggressivity and malignant character. This type of cancer is mostly detected in the metastatic stage. Current treatment options have various side effects, result in the survival rates and quality of life of patients are extremely decreased. Dandelion (Taraxacum officinale (L.) Weber ex F.H. Wigg.) is one of the natural products that has the potential to be therapeutic against a wide range of diseases. This study aimed to evaluate the potential of ethanol extract of dandelion root (DRE) as an alternative anticancer agent. Based on this purpose, milk-rich dandelion roots were collected, cut into small pieces, and then extracted using Soxhlet in the presence of 70% ethanol. The cytotoxic effect of the DRE at certain doses (10, 5, and 2.5 mg/mL) was determined by the Microtetrazolium (MTT) assay for 24, 48, and 72 hours, and half-maximal inhibitory concentration (IC)50 values for these incubation periods were found to be 10 mg/mL, 6.80 mg/mL and 6 mg/mL (p0.001), respectively. As a result, DRE may reduce cell viability when applied to aggressive pancreatic cancer cells and may have the potential to be an alternative anticancer agent. This potential can be clarified with further studies.